Green synthesis of Chrysanthemum morifolium silver nanoparticles and evaluation of its antibacterial activity - Lai, Mun Leong; Ghim, Hock Ong; Khye, Er Loh (Penerbit Universiti Kebangsaan Malaysia, 2024)
The increasing prevalence of microbial infections and antibiotic resistance has sparked interest in investigating the therapeutic potential of silver nanoparticles (AgNPs) as effective antimicrobial agents. The current study seeks to optimize the synthesis of AgNPs using Chrysanthemum morifolium (CM) extract and evaluate their antibacterial activity. Maximum synthesis of CM-AgNPs was achieved using 10 mM of AgNO3 and 20 mg/mL of CM extract at a 6:4 ratio and 3 hr of incubation period at pH 11 and 40°C. The Chrysanthemum morifolium-synthesized silver nanoparticles (CM-AgNPs) displayed a spherical shape, with sizes ranging from 12 to 34 nm. The minimum inhibitory concentration (MIC) against Pseudomonas mirabilis, Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella pneumoniae were 0.0117, 0.0117, 0.0031, and 0.100 mg/mL, respectively. CM-AgNPs demonstrated notable antibiofilm activity of 49.26%, 87.31%, and 66.23% against P. mirabilis, S. aureus, and K. pneumoniae, respectively. These results indicate that CM-AgNPs possess antibacterial properties and hold promise as antimicrobial agents.